Revision of the lanternfly genus Limois Stål, 1863 (Hemiptera: Fulgoromorpha: Fulgoridae) with description of a new species from China - Wang, Wen-Qian; Xu, Si-Long; Constant, Jérôme; Qin, Dao-Zheng (European Journal of Taxonomy, 2020)
All extant species of the planthopper genus Limois Stål (Hemiptera: Fulgoromorpha: Fulgoridae) were studied. One new species, Limois sordida sp. nov., is described and illustrated from China. Six known species are re-described and photos and illustrations of male genitalia are provided. A key to all extant species of this genus is also given.